Hospitalist Management of Vaso-Occlusive Pain Crisis in Patients With Sickle Cell Disease Using a Pathway of Care. Issue 2 (April 2014) - Liles, Edmund Allen; Kirsch, Jonathan; Gilchrist, Michael; Adem, Mukhtar
Abstract: Background: Patients with sickle cell disease (SCD) suffer from intermittent vaso-occlusive pain crises (VOCs). These crises lead to frequent hospitalizations, significant morbidity, and increased mortality risk. Care pathways can enhance efficiency and quality of care. Our study sought to evaluate the development and implementation of a care pathway for patients with SCD experiencing VOCs.Methods: The University of North Carolina (UNC) Comprehensive Sickle Cell Program provides all levels of care for a large population of patients with sickle cell anemia. All patients admitted to UNC Hospitals with SCD VOCs from January 2009 through June 2011 were evaluated. During this time period, we also assessed sequential prospective cohorts during progressive phases of developing and implementing a quality improvement and pathway of care program for this patient population in our study. The developed pathway entailed geographic localization for VOC patients, a single group of faculty physicians caring for these patients, and early use of patient-controlled analgesia (PCA) to achieve pain control. Physicians from the UNC Hospital Medicine Program were responsible for the initiatives. Cohorts were compared to a baseline historical control. Outcomes of interest included patient length of stay (LOS) in the hospital, 30-day readmission rate, need for transfusion, incidence of acute chest syndrome, use of naloxone, and use of PCA.Results: Compared with an historical baseline cohort, the development and implementation of a VOC care pathway for patients with SCD led to reduction in average hospital LOS by 1.44 days ( P < 0.05) and an increase in use of PCAs ( P < 0.05). Patient readmission rates, number of transfusions, incidence of acute chest syndrome, and use of naloxone did not significantly change.Conclusions: Hospitalist-led management of patients with SCD VOCs using a care pathway that emphasizes early, aggressive PCA-based pain control is associated with reduced hospital LOS. The LOS reduction seen in our study is clinically meaningful. Notably, other measures of patient outcomes and quality of care metrics did not change significantly, and some trended towards improvement.